2012
DOI: 10.1105/tpc.112.099945
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Three Arabidopsis ARGONAUTES Using Slicer-Defective Mutants  

Abstract: In RNA-directed silencing pathways, ternary complexes result from small RNA-guided ARGONAUTE (AGO) associating with target transcripts. Target transcripts are often silenced through direct cleavage (slicing), destabilization through slicerindependent turnover mechanisms, and translational repression. Here, wild-type and active-site defective forms of several Arabidopsis thaliana AGO proteins involved in posttranscriptional silencing were used to examine several AGO functions, including small RNA binding, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
237
1
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(263 citation statements)
references
References 58 publications
16
237
1
9
Order By: Relevance
“…Expression of slicer-deficient AGO1 enhances the morphological and molecular phenotypes of the hypomorphic ago1-25 allele (Carbonell et al, 2012). These dominantnegative effects were probably due to competition of the slicer-deficient protein with the residual endogenous AGO1 activity of ago1-25, by sequestration of miRNAs or miRNA-target complexes (Carbonell et al, 2012). A dominant-negative effect on wild-type plants was also described.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Expression of slicer-deficient AGO1 enhances the morphological and molecular phenotypes of the hypomorphic ago1-25 allele (Carbonell et al, 2012). These dominantnegative effects were probably due to competition of the slicer-deficient protein with the residual endogenous AGO1 activity of ago1-25, by sequestration of miRNAs or miRNA-target complexes (Carbonell et al, 2012). A dominant-negative effect on wild-type plants was also described.…”
Section: Resultsmentioning
confidence: 93%
“…Although a low level of slicer activity remained detectable in the E803A mutant (Arribas-Hernández et al, 2016), its phenotype was identical to that of mutants in the other three catalytic residues in all aspects that distinguish them from the null allele. Expression of slicer-deficient AGO1 enhances the morphological and molecular phenotypes of the hypomorphic ago1-25 allele (Carbonell et al, 2012). These dominantnegative effects were probably due to competition of the slicer-deficient protein with the residual endogenous AGO1 activity of ago1-25, by sequestration of miRNAs or miRNA-target complexes (Carbonell et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this, AGO1 and HESO1 colocalize (G. Ren, M. Xie, C. Vinovskis, and B. Yu, unpublished data). We also examined immunoprecipitated miRNAs from an AGO1 slicer-defective mutant (Carbonell et al, 2012) and observed little impact on miR158 tailing, indicating that AGO1 slicer activity is not required to modulate 39 modifications (see Supplemental Figure 6B online). Such 39 modifications occurring without target cleavage are reminiscent of D. melanogaster miRNA truncation and tailing that occurs when extensively matched by a synthetic target mRNA (Ameres et al, 2010).…”
Section: Mutations In Ago1 Suppress the Truncation And Tailing Of Mirnasmentioning
confidence: 98%
“…Data for Columbia, heso1-1, hen1-8, and heso1-1 hen1-8 libraries are from Zhao et al (2012b). IP data from the wild type and catalytic mutants of AGO1 are from Carbonell et al (2012).…”
Section: Accession Numbersmentioning
confidence: 99%
“…Indeed, both viruses and viroids are targeted by the plant RNA-silencing machinery that, through the activity of Dicer-like proteins (DCLs), generates virus-and viroid-derived sRNAs (v-sRNA and vd-sRNA, respectively) of 21-24 nt, which are loaded into AGO (argonaute) proteins to guide the sequence-specific degradation or methylation of cognate RNAs and DNA, respectively (Carbonell et al, 2012;Mallory & Vaucheret, 2010;Minoia et al, 2014;Miozzi et al, 2013;Navarro et al, 2012). Both v-sRNAs and vd-sRNAs accumulating in infecting tissues are therefore molecular markers of ongoing infections by viral and subviral agents.…”
Section: Introductionmentioning
confidence: 99%